Tingkat Pengetahuan Berhubungan dengan Sikap Ibu dalam Toilet Training pada Toddler - Chori Elsera (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
The number of children under ﬁ ve in Indonesia is estimated to reach 30% of the 250 million population of Indonesia. Toddlers who have difﬁ culty in bowel and bladder control (wetting) at preschool age to reach 75 million children. One of the factors that affect toilet training in children under ﬁ ve is mother knowledge about toilet training. Less pengeathuan mothers and families about toilet training can hinder a child’s development in the control of bladder and bowel patterns. The aim of research to know the correlation between knowledge with attitude in toilet training in children ages toddler in the village Glodogan Southern District of Klaten. Descriptive quantitative research with cross sectional approach. Subjects were mothers who have toddler children in the village Glodogan with a total population of 204 people while the study sample as many as 41 respondents using purposive sampling technique. The research was conducted on 28 July-2 August 2012 in the village Glodogan Southern District of Klaten. The research instrument was a questionnaire. Processing data using bivariate analysis using chi square. The results obtained from this study is a good level of knowledge. The attitude of most of the respondents supporting toilet training. There is a relationship between knowledge with attitude mother in toilet training in children ages toddler in the village Glodogan Southern District of Klaten. Conclusion no relationship between the level of knowledge of the attitude of the mother in toilet training in children ages toddler in the village Glodogan Southern District of Klaten.